Imperatives of Efficient Use of Land and Resource Potential of the Agricultural Enterprises of Ukraine - Vinichenko, Igor; Tkachenko, Serhii; Sereda, Oleksandr; Prus, Yurii; Прус, Юрій Олександрович; Pochernina, Nataliia; Почерніна, Наталя Вікторівна (Polissia National University, 2021)
EN: The article considers the institutionalization of land relations and the imperatives of efficient use of land and resource potential of agricultural enterprises of Ukraine. Within the institutionalization of land relations, the methodical approach to complex estimation of effective use of land and resource potential of agricultural enterprises is substantiated, by definition of an integral indicator of efficiency (quantitative and qualitative characteristics of involved resources, productivity and efficiency) of basic kinds of activity of economic entities on agricultural lands. Indicators of transparency in the assessment of land and resource potential and indicators of land policy according to the level of their use in agriculture are proposed. Comprehensive criteria for assessing the components of the efficiency of the use of land and resource potential of agricultural enterprises are presented. The amount of rent for land shares and the amount of fertilizer application per 1 ha of sown area of agricultural enterprises of Ukraine are analyzed. The productive capacity of natural and potential yields for grain and legumes (excluding corn for grain) in Ukraine has been determined. The normative monetary value of 1 ha of arable land in rural areas is calculated on average for one region of Ukraine, adjusted for the natural yield of cereals and legumes, without taking into account the application of fertilizers. The forecast level of technical, social and economic efficiency of the use of land and resource potential of agricultural enterprises is presented./////////////UK:У статті розглянуто інституціоналізацію земельних відносин та імперативи ефективного використання земельного та ресурсного потенціалу сільськогосподарських підприємств України. У межах інституціоналізації земельних відносин обґрунтовано методичний підхід до комплексної оцінки ефективного використання земельного та ресурсного потенціалу сільськогосподарських підприємств шляхом визначення інтегрального показника ефективності (кількісних та якісних характеристик залучених ресурсів, продуктивності та ефективності) основних видів діяльності суб’єктів господарювання на землях сільськогосподарського призначення. Запропоновано показники прозорості оцінки земельного та ресурсного потенціалу та показники земельної політики відповідно до рівня їх використання у сільському господарстві. Представлені комплексні критерії оцінки складових ефективності використання земельних ресурсів та ресурсного потенціалу сільськогосподарських підприємств. Проаналізовано розмір орендної плати за земельні паї та обсяг внесення добрив на 1 га посівної площі сільськогосподарських підприємств України. Визначено виробничі можливості природних і потенційних врожаїв зернових і зернобобових культур (крім кукурудзи на зерно) в Україні. Нормативна грошова вартість 1 га ріллі в сільській місцевості розраховується в середньому за одним регіоном України з поправкою на природну врожайність зернових та зернобобових культур без урахування внесення добрив. Представлено прогнозний рівень технічної, соціальної та економічної ефективності використання земельного й ресурсного потенціалу сільськогосподарських підприємств.
Імперативи ефективного використання земельного та ресурсного потенціалу сільськогосподарських підприємств України